ANALISIS PENGGUNAAN PENILAIAN AUTENTIK DALAM PEMBELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN PADA KURIKULUM 2013 REVISI KELAS X DI SMA NEGERI 1 KARTASURA TAHUN AJARAN 2016/2017 - Ambarwati, Nela, Wijianto, Winarno (Prodi PPKn FKIP UNS, 2017)
ABSTRACTThe objectives of this research are to 1) investigate the authentic assessment using in Pancasila and Civic Education learning 10th grade at SMA N 1 Kartasura, 2) investigate the teacher?s constraints in the authentic assessment using in Pancasila and Civic Education learning 10th grade at SMA N 1 Kartasura, 3) investigate the teacher?s efforts to deal with the constraints in the authentic assessment using in Pancasila and Civic Education learning 10th grade at SMA N 1 Kartasura. This research used the descriptive qualitative research method with the case study approach. Its subjects were Pancasila and Civic Education matter teachers of SMA N 1 Kartasura. The samples of research were determined by using the in-depth interview, observation, and documentation study. The validity of the data was tested by using the interactive model of analysis. The results of research showes as follows. (1) Authentic assessment using in Pancasila and Civic Education learning 10th grade at SMA N 1 Kartasura has not been done according to the procedures in 2013 revision curriculum. Authentic assessment procedures include the planning, implementation, and analysis and reporting of the assessment. (2) The teacher?s constraints in the authentic assessment using in Pancasila and Civic Education learning 10th grade at SMA N 1 Kartasura known from the authentic assessment procedure which includes assessment planning, assessment implementation, and analysis as well as assessment reporting. (3) Teacher?s effort to deal with the assessment eplanning constraints are asking to other teachers more competent and make an assessment instrument according to the teacher's ability but to measure the competence of learners authentically. To deal with the assessment implementation constraints are to limit the components of attitudes to be assessed at each meeting and to divide the time before all presentation groups. While, to deal with the and reporting of the assessment constraits are making the description of the short and clear, and use the best time to quickly recap the value and classify it into each aspect, both knowledge, attitude, as well as skills. Keywords: Using, Teacher?s Constraints, Teacher?s Efforts, Authentic Assessments, and Pancasila and Civic Education learning